Impact of a Pharmacist-led Educational Intervention on knowledge of antibiotics among mothers of under-five children attending vaccination clinics in Delta State, Nigeria (Nigerian Journal of Pharmaceutical Research, 2022)
Background.  The extent of mothers’ knowledge about antibiotics largely determines their use in children.Objectives. This study assessed knowledge of antibiotics among mothers’ of under-fives and the immediate impact of a pharmacist-led educational intervention on knowledge scoresMethods. A prospective interventional study was conducted among mothers of under-five children. The pre-intervention knowledge scores were determined with the aid of an antibiotic knowledge questionnaire which was interviewer-administered. An educational intervention which focused on all aspects of knowledge of antibiotic use covered by the questionnaire was administered by a pharmacist; thereafter the post intervention knowledge scores were determined using the same knowledge questionnaire. Overall knowledge scores were categorized into poor, moderate and good. The percentage change in the proportions of mothers who had good scores was determined,   Chi square test were performed to determine the relationship between knowledge scores and having a family member as a healthcare professional and paired t-test was done to determine impact of the intervention on the mean scores on each knowledge question. P values ≤ 0.05 were statistically significant.Results. A total of 253 mothers participated in the study from two centres. Twenty-one mothers (7.7%) had good knowledge on antibiotics at baseline which increased to 138 (50.6%) after an educational intervention. Knowledge scores for each item also  improved post-intervention with least pre-intervention mean scores increasing from 0.25(SD=0.44) to 0.67(SD=0.47), p